A New Design of Education in The Context of The Covid-19 Crisis - Amalia Venera TODORUT; Gabriela DOBROTA (Communications of International Proceedings, 2020)
The paper addresses a strictly topical issue regarding the need to reconfigure education in the context of the Coronavirus (COVID-19) crisis the fundamental objective of the paper is to highlight the role of universities in providing the necessary tools and ways of learning and development, in a completely different context to what is practiced until now. In the paper, we specify the importance of digital learning and characterize the standards for students and teachers for the implementation of online education. We also show future trends in the field of education and analyse a questionnaire applied to 114 European universities focusing on the impact of the coronavirus crisis on higher education. We also present aspects related to online learning practiced at "Constantin Brâncuși" University, through the analysis of a questionnaire applied to the main educational actors. The investigation methods materialized in the documentary and comparative analysis of the data and information provided by reports, statistics, specialized articles and in the application and interpretation of some questionnaires.
Keywords: digital education; innovation; universities; creativity